Reconstructing the Traumatized Subject: a Lacanian Psychoanalytic Research of Identity Formation in Scott Derrickson’s The Black Phone (2021) - Dina Amelia; Bagus Herlambang (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Trauma is frequently related to psychological distress and identity instability. Trauma, according to psychoanalytic theory, can also be used to reconstruct one's identity. This study seeks to examine Finney Blake's transition in The Black Phone (2021) using Jacques Lacan's notions of the Real, Symbolic, and Imaginary. Using a qualitative descriptive method and a literary psychoanalytic approach, this study explores chosen scenes, dialogues, and symbolic aspects through close examination. The findings indicate that Finney's trauma depicts the Real through his feelings of fear, isolation, and helplessness. The black phone serves as a symbolic medium, providing language, information, and a connection to prior victims, allowing Finney to reconstitute his identity. Furthermore, the Imaginary depicts Finney's shift from powerless victim to active person with agency. This study demonstrates that trauma in horror narratives not only represents destruction, but it can also help to shape a new subject. Keywords: identity reconstruction, Lacanian psychoanalysis; subjectivity; The Black Phone; trauma